The Northern Russian pragmatic particle dak in the dialect of Varzuga (Kola Peninsula). An information structuring device in informal spontaneous speech - Post, Margje (Universitetet i Tromsø, 2006)
The Northern Russian pragmatic particle dak presents a good case of how particles are used to structure information in informal language. It exemplifies that connectives can mark relations to concepts lacking a concrete linguistic form. The research presented here is based on a sound corpus of the dialect of Varzuga, an old Russian Pomor settlement on the White Sea coast. For the first time, prosodic analysis and recent theories on information structure and pragmatic particles were applied to describe a Russian dialectal particle. Dak can be described as a procedural marker, signalling how the information implied in the expression it is attached to relates to other accessible information. The particle is used in many different contexts and positions in the utterance, but it was found to always contribute to an utterance with the same core meaning. Dak signals an asymmetric relation between two information units, x and y, and that y is based on x. Examples of x and y are cause and consequence, condition and event and a dialect word and its explanation. X and y are often set up against alternatives. The specific content of the implied relation is determined by the context. X and y should not be understood as linguistic expressions, but as mental units, since they seldom both have a linguistic expression. Dak is always prosodically attached to the linguistic representation of x or y, or to both, and takes a fixed position relative to these expressions. Dak is compared to other particles used in the dialect, like da, tak, -to and ved’, which all give a slightly different contribution to an utterance. The thesis also contains a general description of the village of Varzuga and of its endangered dialect, and some sample texts. Sound files can be downloaded from the author’s website (http://uit.no/humfak/tilsette/95).